Rabies in Kazakhstan. - Akmetzhan A Sultanov; Sarsenbay K Abdrakhmanov; Aida M Abdybekova; Bolat S Karatayev; Paul R Torgerson (Public Library of Science (PLoS), 2016)
BACKGROUND:Rabies is a neglected zoonotic disease. There is a sparsity of data on this disease with regard to the incidence of human and animal disease in many low and middle income countries. Furthermore, rabies results in a large economic impact and a high human burden of disease. Kazakhstan is a large landlocked middle income country that gained independence from the Soviet Union in 1991 and is endemic for rabies. METHODOLOGY/PRINCIPAL FINDINGS:We used detailed public health and veterinary surveillance data from 2003 to 2015 to map where livestock rabies is occurring. We also estimate the economic impact and human burden of rabies. Livestock and canine rabies occurred over most of Kazakhstan, but there were regional variations in disease distribution. There were a mean of 7.1 officially recorded human fatalities due to rabies per year resulting in approximately 457 Disability Adjusted Life Years (DALYs). A mean of 64,289 individuals per annum underwent post exposure prophylaxis (PEP) which may have resulted in an additional 1140 DALYs annually. PEP is preventing at least 118 cases of human rabies each year or possibly as many as 1184 at an estimated cost of $1193 or $119 per DALY averted respectively. The estimated economic impact of rabies in Kazakhstan is $20.9 million per annum, with nearly half of this cost being attributed to the cost of PEP and the loss of income whilst being treated. A further $5.4 million per annum was estimated to be the life time loss of income for fatal cases. Animal vaccination programmes and animal control programmes also contributed substantially to the economic losses. The direct costs due to rabies fatalities of agricultural animals was relatively low. CONCLUSIONS/SIGNIFICANCE:This study demonstrates that in Kazakhstan there is a substantial economic cost and health impact of rabies. These costs could be reduced by modifying the vaccination programme that is now practised. The study also fills some data gaps on the epidemiology and economic effects of rabies in respect to Kazakhstan.